GAMBARAN PENGETAHUAN, SIKAP, PERILAKU DAN KONVERSI PENDERITA TUBERKULOSIS PARU BAKTERI TAHAN ASAM (BTA) POSITIF DI KOTA DENPASAR TAHUN 2012 - Ni Luh Nyoman Tri Astuti Pradnyadewi; I Wayan Gede Artawan Eka Putra (ARCHIVE OF COMMUNITY HEALTH, 2013)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Sucessful treatmentof pulmonary TB does not only depend on medical aspects but also social aspects such as lack of knowledge, attitude, and behavior of TB patients. Denpasar has the lowest success conversion rate of new smear-positive Pulmonary TB from the year 2008 to 2010 compared to otherdistrictspulmonary TB patients and its relation to the conversion of smear-positive pulmonary TB inDenpasar 2012.This study was a descriptive cross sectional study. The samples were 82 smear-positivepulmonary TB patients that has been treated according to DOTS strategy in Denpasar in 2012.Samples were selected by cluster random sampling. Data were collected through interviews witha questionnaire and analyzed by descriptive and chi-square test with 5% signifi cance.The results indicated the majority (89%) of patients with pulmonary TB have high knowledge about TB and with mostly good attitudes (78%). However, pateints who have good behavior regarding TB disease is about 46.3%. The conversion rate of TB patients in the city of Denpasaris 68.3%. In addition, there was a signifi cant relationship between behavior to conversion smearpositivepulmonary TB (p = 0.004, CI 95% = 1.548 – 12.761).IEC is needed targeting the pulmonary TB patient about the TB disease, transmission mode,prevention and transmission to change the current behavior regarding TB treatment.